Baseline levels of dynamic CD4+ T cell adhesion to MAdCAM-1 correlate with clinical response to vedolizumab treatment in ulcerative colitis: a cohort study - Allner, Clarissa; Melde, Michaela; Becker, Elisabeth; Fuchs, Friederike; Mühl, Laura; Klenske, Entcho; Müller, Lisa; Morgenstern, Nadine; Fietkau, Konstantin; Hirschmann, Simon; Atreya, Raja; Atreya, Imke; et al. (BMC Gastroenterology, 2020)
BACKGROUND: While the number of therapeutic options for treating inflammatory bowel diseases (IBD) is increasing, evidence for rational treatment decisions is scarce in many cases. In particular, appropriate biomarkers to predict the response to the anti-α4β7 integrin antibody vedolizumab are currently lacking. METHODS: We performed a cohort study with 21 patients suffering from ulcerative colitis (UC), in which first-time treatment with vedolizumab was initiated. CD4+ T cells were isolated from the peripheral blood and dynamic adhesion to recombinant mucosal vascular addressin cell adhesion molecule (MAdCAM-)1 in vitro as well as the effect of vedolizumab on such adhesion in vitro was determined. The expression of α4β1 integrin on peripheral blood CD4+ T cells was quantified by flow cytometry. Electronic patient records were reviewed to determine clinical response to vedolizumab. RESULTS: Dynamic adhesion of peripheral blood CD4+ T cells to MAdCAM-1 and the reduction of adhesion following vedolizumab treatment in vitro were higher and the change in α4β1 expression on CD4+ T cells was different in vedolizumab responders and non-responders. Responders could be identified with high specificity and positive-predictive value. CONCLUSIONS: Determining dynamic adhesion of CD4+ T cells to MAdCAM-1 and the in vitro response to vedolizumab before treatment initiation or dynamic integrin regulation in the early course of treatment seem to be promising tools to predict the clinical response to vedolizumab therapy. Larger prospective studies are warranted.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Adhesion; Gut homing; Inflammatory bowel diseases; T cells; Vedolizumab

Circulating Adaptive Immune Cells Expressing the Gut Homing Marker α4β7 Integrin Are Decreased in COVID-19 - Müller, Tanja; Becker, Elisabeth; Wiendl, Maximilian; Schulze, Lisa; Voskens, Caroline; Kremer, Andreas; Neurath, Markus; Zundler, Sebastian; Völkl, Simon (Frontiers in Immunology, 2021)
Background: Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a wide range of symptoms including gastrointestinal manifestations, and intestinal epithelial cells are a target of the virus. However, it is unknown how the intestinal immune system contributes to systemic immune responses in coronavirus disease 2019 (COVID-19). Methods: We characterized peripheral blood lymphocytes from patients with active COVID-19 and convalescent patients as well as healthy controls by flow cytometry. Results: The frequency and absolute number of circulating memory T and B cells expressing the gut homing integrin α4β7 integrin was reduced during COVID-19, whether gastrointestinal symptoms were present or not. While total IgA-expressing B cells were increased, gut-imprinted B cells with IgA expression were stable. Conclusion: COVID-19 is associated with a decrease in circulating adaptive immune cells expressing the key gut homing marker α4β7 suggesting that these cells are preferentially recruited to extra-intestinal tissues independently of α4β7 or that the systemic immune response against SARS-CoV-2 is at least numerically dominated by extraintestinal, particularly pulmonary, immune cell priming.
CRIS-Team Scopus Importer:2021-05-21
Keywords: COVID-19; gut homing; integrins; SARS-CoV-2 infection; T cell trafficking

Clinical experiences and predictors of success of treatment with vedolizumab in IBD patients: a cohort study - Mühl, Laura; Becker, Elisabeth; Müller, Tanja; Atreya, Raja; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (BMC Gastroenterology, 2021)
Background: Vedolizumab has become a standard treatment for the inflammatory bowel diseases ulcerative colitis (UC) and Crohn’s disease (CD). However, there is an ongoing debate on the ideal individual treatment algorithms and means to predict treatment response are not routinely established. Aims: We aimed to describe our experiences with vedolizumab at a large German tertiary referral center and to identify clinical predictors of success of vedolizumab treatment. Methods: We performed a retrospective single-center cohort study employing univariable and multivariable analyses as well as Kaplan–Meier analyses of persistence on treatment. Results: 36% and 35% of the patients with UC and CD, respectively, reached clinical remission after 17 weeks. Patients with lower clinical disease activity were more likely to achieve remission. The median persistence on treatment was 33 months for UC and 29 months for CD. Conclusion: Our study confirms that vedolizumab is an efficient option for the treatment of UC and CD. Clinical parameters of disease activity may help to predict the success of treatment.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Inflammatory bowel diseases; Real-world data; Vedolizumab

Dose-dependent differential effects of vedolizumab therapy on adhesion of regulatory and effector T cells - Becker, Elisabeth; Wiendl, Maximilian; Schulz-Kuhnt, Anja; Atreya, I.; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10

Dynamic Adhesion Assay for the Functional Analysis of Anti-adhesion Therapies in Inflammatory Bowel Disease - Becker, Elisabeth; Schramm, Simon; Binder, Marie-Theres; Allner, Clarissa; Wiendl, Maximilian; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Journal of Visualized Experiments, 2018)
Gut homing of immune cells is important for the pathogenesis of inflammatory bowel diseases (IBD). Integrin-dependent cell adhesion to addressins is a crucial step in this process and therapeutic strategies interfering with adhesion have been successfully established. The anti-α4β7 integrin antibody, vedolizumab, is used for the clinical treatment of Crohn's disease (CD) and ulcerative colitis (UC) and further compounds are likely to follow. The details of the adhesion procedure and the action mechanisms of anti-integrin antibodies are still unclear in many regards due to the limited available techniques for the functional research in this field. Here, we present a dynamic adhesion assay for the functional analysis of human cell adhesion under flow conditions and the impact of anti-integrin therapies in the context of IBD. It is based on the perfusion of primary human cells through addressin-coated ultrathin glass capillaries with real-time microscopic analysis. The assay offers a variety of opportunities for refinements and modifications and holds potentials for mechanistic discoveries and translational applications.
EVALuna2:207768

Immune cell trafficking and retention in inflammatory bowel disease: Mechanistic insights and therapeutic advances - Zundler, Sebastian; Becker, Elisabeth; Schulze, Lisa; Neurath, Markus (Gut, 2019)
Intestinal immune cell trafficking has been identified as a central event in the pathogenesis of inflammatory bowel diseases (IBD). Intensive research on different aspects of the immune mechanisms controlling and controlled by T cell trafficking and retention has led to the approval of the anti-α4β7 antibody vedolizumab, the ongoing development of a number of further anti-trafficking agents (ATAs) such as the anti-β7 antibody etrolizumab or the anti-MAdCAM-1 antibody ontamalimab and the identification of potential future targets like G-protein coupled receptor 15. However, several aspects of the biology of immune cell trafficking and regarding the mechanism of action of ATAs are still unclear, for example, which impact these compounds have on the trafficking of non-lymphocyte populations like monocytes and how precisely these therapies differ with regard to their effect on immune cell subpopulations. This review will summarise recent advances of basic science in the field of intestinal immune cell trafficking and discuss these findings with regard to different pharmacological approaches from a translational perspective.
CRIS-Team Scopus Importer:2019-06-18
Keywords: cell adhesion; Crohn's disease; inflammatory bowel disease; integrins; ulcerative colitis

Non-classical monocyte homing to the gut via α4β7 integrin mediates macrophage-dependent intestinal wound healing - Schleier, Lena; Wiendl, Maximilian; Heidbreder, Karin; Binder, Marie Theres; Atreya, Raja; Rath, Timo; Becker, Elisabeth; Schulz-Kuhnt, Anja; Stahl, Annette; Schulze, Lisa; Ullrich, Karen; Merz, Simon F.; et al. (Gut, 2019)
Objective: To study the role of α4β7 integrin for gut homing of monocytes and to explore the biological consequences of therapeutic α4β7 inhibition with regard to intestinal wound healing. Design: We studied the expression of homing markers on monocyte subsets in the peripheral blood and on macrophage subsets in the gut of patients with IBD and controls with flow cytometry and immunohistochemistry. Integrin function was addressed with dynamic adhesion assays and in vivo gut homing assays. In vivo wound healing was studied in mice deficient for or depleted of α4β7 integrin. Results: Classical and non-classical monocytes were clearly dichotomous regarding homing marker expression including relevant expression of α4β7 integrin on human and mouse non-classical monocytes but not on classical monocytes. Monocyte-expressed α4β7 integrin was functionally important for dynamic adhesion to mucosal vascular addressin cell adhesion molecule 1 and in vivo gut homing. Impaired α4β7-dependent gut homing was associated with reduced (effect size about 20%) and delayed wound healing and suppressed perilesional presence of wound healing macrophages. Non-classical monocytes in the peripheral blood were increased in patients with IBD under clinical treatment with vedolizumab. Conclusion: In addition to reported effects on lymphocytes, anti-α4β7 therapy in IBD also targets non-classical monocytes. Impaired gut homing of such monocytes might lead to a reduction of wound healing macrophages and could potentially explain increased rates of postoperative complications in vedolizumab-treated patients, which have been observed in some studies.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Crohn's disease; gut immunology; inflammatory bowel disease; surgery for IBD; ulcerative colitis

Targeting Immune Cell Trafficking – Insights From Research Models and Implications for Future IBD Therapy - Wiendl, Maximilian; Becker, Elisabeth; Müller, Tanja; Voskens, Caroline; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs), including Crohn’s disease (CD) and ulcerative colitis (UC) are multifactorial diseases with still unknown aetiology and an increasing prevalence and incidence worldwide. Despite plentiful therapeutic options for IBDs, the lack or loss of response in certain patients demands the development of further treatments to tackle this unmet medical need. In recent years, the success of the anti-α4β7 antibody vedolizumab highlighted the potential of targeting the homing of immune cells, which is now an important pillar of IBD therapy. Due to its complexity, leukocyte trafficking and the involved molecules offer a largely untapped resource for a plethora of potential therapeutic interventions. In this review, we aim to summarise current and future directions of specifically interfering with immune cell trafficking. We will comment on concepts of homing, retention and recirculation and particularly focus on the role of tissue-derived chemokines. Moreover, we will give an overview of the mode of action of drugs currently in use or still in the pipeline, highlighting their mechanisms and potential to reduce disease burden.
CRIS-Team Scopus Importer:2021-06-04
Keywords: homing; IBD; retention; T cell; therapy; trafficking